Natural killer cell engagers for cancer immunotherapy - Nikkhoi, Shahryar Khoshtinat; Li, Geng; Hatefi, Arash (Frontiers in Oncology, 2025)
This review article explores the rapidly evolving field of bi-, tri-, and multi-specific NK cell engagers (NKCEs), highlighting their potential as a cutting-edge approach in cancer immunotherapy. NKCEs offer a significant advancement over conventional monoclonal antibodies (mAbs) by enhancing Antibody-Dependent Cellular Cytotoxicity (ADCC). They achieve this by stably and selectively binding to both NK cell activating receptors and tumor-associated antigens (TAAs). Unlike traditional mAbs, which depend on the relatively transient interaction between their Fc region and CD16a, NKCEs establish more robust connections with a range of activating receptors (e.g., CD16a, NKG2D, NKp30, NKp46, NKG2C) and inhibitory receptors (e.g., Siglec-7) on NK cells, thereby increasing cancer cell killing efficacy and specificity. This review article critically examines the strategies for engineering bi-, tri-, and multi-specific NKCEs for cancer immunotherapy, providing an in-depth analysis of the latest advancements in NKCE platform technologies currently under development by pharmaceutical and biotech companies and discussing the preclinical and clinical progress of these products. While NKCEs show great promise, the review underscores the need for continued research to optimize their therapeutic efficacy and to overcome obstacles related to NK cell functionality in cancer patients. Ultimately, this article presents an overview of the current landscape and future prospects of NKCE-based cancer immunotherapy, emphasizing its potential to revolutionize cancer treatment.